2016
DOI: 10.1080/10447318.2016.1186306
|View full text |Cite
|
Sign up to set email alerts
|

Theory, Practice and Policy: An Inquiry into the Uptake of HCI Practices in the Software Industry of a Developing Country

Abstract: With almost four decades of existence as a community, human-computer interaction (HCI) practice has yet to diffuse into a large range of software industries globally. A review of existing literature suggests that the diffusion of HCI practices in software organizations lacks theoretical guidance. Although many studies have tried to facilitate HCI uptake by the software industry, there are scarce studies that consider HCI practices as innovations that software organizations could or should adopt. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The results show intermediate level of usability awareness and the limited knowledge of HCI practices. Another study was conducted to find the understanding and awareness level of HCI [20]. The results show that HCI practices and processes are at their beginning level in most of software houses.…”
Section: Related Workmentioning
confidence: 99%
“…The results show intermediate level of usability awareness and the limited knowledge of HCI practices. Another study was conducted to find the understanding and awareness level of HCI [20]. The results show that HCI practices and processes are at their beginning level in most of software houses.…”
Section: Related Workmentioning
confidence: 99%
“…Even with the continual call for the inversion of design paradigms and lenses in HCI and CSCW, few studies from Nigeria have examined the design and development frames informing the work of software practitioners [24,[26][27][28]. What these studies have shown are the assumptions and principles shaping the practice of the community; specifcally, the (mis)understanding of 'user's', 'cultures' and 'politics' in design and the approaches adopted and used for designing, developing and evaluating tools.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the perception of knowledge about HCI and/or the use of HCI approaches in practice. We found 12 studies in literature using an ad hoc technique . These studies were not developed in the context of software development with SPCM model implementations.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were not developed in the context of software development with SPCM model implementations. They show the practice of HCI, usability, and user experience (UX) in the industry for different countries (Korea, Switzerland, Germany, Italy, Nigeria, Malaysia, Brazil, and the United States and European countries), showing the difficulties and benefits of HCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation